Pengaruh Interaksi Teman Sebaya Terhadap Hasil Belajar PAI Peserta Didik Kelas X MA Darul Ma’arif Miru Kedamean Gresik - Sofitri Isruroh; Imam Bahrozi; Muhammad Indra Adi Gunawan; Muhammad Arifudin (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This research aims to find out whether peer interaction influences PAI learning outcomes for class X students at MA Darul Ma'arif Miru Kedamean Gresik. The independent variable in this research is Peer Interaction. Meanwhile, the dependent variable in this research is PAI Learning Outcomes. To obtain the information needed to prepare the research, the author used a quantitative research method to determine the influence of the independent variable (X) on the dependent variable (Y) by collecting data using a survey method by distributing questions/statements in the form of a questionnaire. The population in this study were students of class X MA Darul Ma'arif Miru Kedamean Gresik. The research sample was all Class X B students with the sampling technique used was purposive sampling so that the sample used in the research was 34 respondents. The research results show that the regression coefficient value of the independent variable peer interaction (X) with the dependent variable PAI learning outcomes (Y) is 0.655, meaning that if peer interaction increases by one unit, learning outcomes will increase by 0.655. The regression coefficient is positive between peer interaction and learning outcomes. This shows that if peer interaction increases, learning outcomes will also increase. The data analysis technique used can determine the measurement scale of each variable, so that hypothesis testing can be carried out appropriately. So the results of research and data analysis show that the influence of peer interaction variables on learning outcomes is 0.144 (14.4%) while 85.6% is influenced by other variables outside the research model. Keywords: Peer Interaction, Learning Outcomes,PAI Subjects